ESA e l'utilizzo di tecnologia Grid e SOA per l'Osservazione della Terra - Cossu, Roberto; Fusco, Luigi (GEOmedia, 2009)
ESA grid and SOA Technologies for Earth Observation Due to its intensive data processing and highly distributed organization, the multidisciplinary Earth Science (ES) applications community is uniquely positioned for the uptake and exploitation of Grid technologies. This article describes a number of initiatives that the European Space Agency is carrying focusing on a ES e-collaboration platform that makes use of Grid and SOA technologies. Starting from the experience gained so far with ESA Grid Processing on Demand, we will discuss the vision of a dedicated ES platform. The aim is to enable scientists to locate, access, combine and integrate historical and fresh Earth-related data from space, airborne and in-situ sensors archived in large distributed repositories. The big challenge is to allow Earth Science communities to easil and quickly derive objective information and share knowledge based on all environmentally sensitive domains. The GENESIDR project is already taking important steps in developing this platform.